Dampak PT. Virtue Dragon Nickel Industry Terhadap Kondisi Sosial Ekonomi Petani Sayur-Sayuran di Desa Morosi Kecamatan Morosi Kabupaten Konawe - Dida, Haswan; Salam, Idrus; Zani, Munirwan (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
This study aims to analyze the impact of PT. Virtue Dragon Nickel Industry on Socio-Economic Conditions Farmer (Case on Farmer Vegetables in the Morosi village, Morosi District, Konawe regency). The research was conducted in October to December 2016, with a sample of 35 farmers and Village Head as the informants. Data were obtained through a questionnaire to provide a list of questions to the farmers of vegetables and it analyzed by descriptive qualitative and quantitative. The variables were observed in this study, generally include: age, formal education, number of dependents, and farming experience. While the observed variables to analyze the impact of PT. Virtue Dragon Nickel Industry on Economic Social Farmers are qualitative analysis include: education and health, business opportunities, employment and income to calculate the kuantitataf analyzed. The results indicate that the presence of PT. Virtue Dragon Nickel Industry has positive impacts and negative impacts on society of Morosi Rural District, Konawe regency. Positive Impact in which community acquired are a lot of business opportunities, employment, and increasement ofÂ  income of farmers vegetables. While the negative impact are the declining quality of air circulation which is caused by the activities of mining companies, and there were not improvements in schools and health care facilities yet in the village of Morosi, Morosi Districi, Konawe Regency